Trucking System VS. Conveyor System for Coal Material Transportation in PT. Bukit Asam Coal Mines - Hendriyan, Fiet (Universitas KH. Abdul Chalim Mojokerto, 2025)
PT Bukit Asam Tbk (PTBA), a major state-owned coal producer, has set an ambitious target to increase coal output from 40 million tons in 2024 to 100 million tons by 2029. Using a quantitative research design, the study applies capital budgeting tools such as Net Present Value (NPV), Internal Rate of Return (IRR), and Incremental Analysis, along with risk evaluation methods including sensitivity analysis, scenario analysis, and Monte Carlo simulations. The analysis reveals that transitioning to a conveyor system yields a significant NPV advantage of IDR 6.57 trillion and an incremental IRR of 19.97%, surpassing the project's hurdle rate. Monte Carlo results indicate a 71% probability of achieving positive NPV, affirming the conveyor system’s robustness under financial uncertainty. Beyond financial returns, the conveyor alternative offers operational improvements such as lower emissions, higher safety, and more reliable throughput. This feasibility study concludes that the conveyor-based system is both economically and strategically superior, aligning with PTBA’s long-term goals for cost efficiency, environmental responsibility, and production scalability.